Designing and evaluating mobile Iqra application prototype / Rafidah Isa - Isa, Rafidah (2013)
The aim of this IT Project is to design the prototype for mobile Iqra application specifically for preschoolers in order to support them to learn Iqra trough mobile devices. It is specifically developed for Android platform with fun interface elements. The interface of the prototype was developed based on the concept of designing for fun and in line with the mobile design guideline as well as the design guideline for children. The content of the application covered the introduction of Hijaiyah letters, the three basic punctuation marks which are fathah, kasroh and dommah as well games in order to measure their proficiency level of each of the lesson learned. The application will guide the users to pronounce each of the letters and the phonic sounds of the Hijiyah letters. Since there is a gap of interpreting the object between the adult designers and young users, level of fun was measured among the users using quantitative and qualitative methods. Based on the finding the prototyped developed had successfully meet the needs and expectation of the children when more than three quarter of the respondent responded that the application was fun and show their interest use the application again in the future. However, there still have rooms for improve for future work. The application may later develop for other mobile operating system so that more users can use the application without restriction to only Android platform.